2003
DOI: 10.1002/jssc.200301465
|View full text |Cite
|
Sign up to set email alerts
|

Improved separation and quantitative determination of hydrocarbon types in gas oil by normal phase high‐performance TLC with UV and fluorescence scanning densitometry

Abstract: Improved separation and quantitative determination of hydrocarbon types in gas oil by normal phase high-performance TLC with UV and fluorescence scanning densitometry Improved methods for separation and quantitative determination of hydrocarbon types from gas oil have been developed, which were based on high-performance thin-layer chromatography with ultraviolet and fluorescence scanning densitometry using horizontal elution. One of the methods allows the separation, detection, and determination of alkanes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 10 publications
(18 reference statements)
0
30
0
Order By: Relevance
“…As shown throughout this work, fluorescent response depends on the balance between non-specific and specific interactions in each particular case between probe and analyte in the medium considered. For a given system, it has been reported that the sign and magnitude of analyte response can be tailored by modification of chromatographic parameters: [4,6,7] probe concentration, scanning beam size, probe structure and its optical characteristics (l exc and l em ), sample structure, sample concentration and application volume. Additionally, the development length and sample application system have an influence on peak width, and hence detection sensitivity, and also influence the fluorescent response.…”
Section: Fluorophoresmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown throughout this work, fluorescent response depends on the balance between non-specific and specific interactions in each particular case between probe and analyte in the medium considered. For a given system, it has been reported that the sign and magnitude of analyte response can be tailored by modification of chromatographic parameters: [4,6,7] probe concentration, scanning beam size, probe structure and its optical characteristics (l exc and l em ), sample structure, sample concentration and application volume. Additionally, the development length and sample application system have an influence on peak width, and hence detection sensitivity, and also influence the fluorescent response.…”
Section: Fluorophoresmentioning
confidence: 99%
“…[2 ,4-6] For example, a TLC method has been developed for separating and determining saturated hydrocarbons in fossil-fuel products by fluorescence scanning densitometry, through pre-or post-impregnation of silica gel plates with berberine or coralyne salts. [7] The aim of recent work by us [8] was to develop original HPTLC-based methods for separating lipids, using FDIC for detection. FDIC was used here in combination with different automated multiple development (HPTLC/AMD) strategies for separating lipids on silica gel plates.…”
Section: Introductionmentioning
confidence: 99%
“…7. According to [19,25] the obtained data can be interpreted as a distribution of aromatic and heteroaromatic hydrocarbons. Chromatograms show that co-hydropyrolysis products are characterised by higher content of benzene derivatives (region A in Fig.…”
Section: Characterization Of Middle Liquid Hydrocarbon Products (Fracmentioning
confidence: 99%
“…Saturated hydrocarbons produce increases in berberine or Reichardt's dye emission [2]. It has been possible to use this phenomenon in HPTLC-scanning fluorescence mode, by impregnating silica gel plates with the above-mentioned probes for determining saturated hydrocarbons in different types of fuels [5,6]. Fluorescent responses in these systems depend on analyte structure through the interactions that they establish with the corresponding probe.…”
Section: Introductionmentioning
confidence: 99%